Phosphoric Acid Loaded Azo (−NN−) Based Covalent Organic Framework for Proton Conduction - Chandra, Suman; Kundu, Tanay; Kandambeth, Sharath; BabaRao, Ravichandar; Marathe, Yogesh; Kunjir, Shrikant M; Banerjee, Rahul (Journal of the American Chemical Society, 2014)
Two new chemically stable functional crystalline covalent organic frameworkds (COFs) (Tp-Azo and Tp-Stb) were synthesized using the Schiff base reaction between triformylphloroglucinol (Tp) and 4,4′-azodianiline (Azo) or 4,4′-diaminostilbene (Stb), respectively. Both COFs show the expected keto-enamine form, and high stability toward boiling water, strong acidic, and basic media. H3PO4 doping in Tp-Azo leads to immobilization of the acid within the porous framework, which facilitates proton conduction in both the hydrous (σ = 9.9 × 10–4 S cm–1) and anhydrous state (σ = 6.7 × 10–5 S cm–1). This report constitutes the first emergence of COFs as proton conducting materials.